Correlation between movement complexity during static standing and balance function in institutionalized older adults - Yamagata M (Dove Medical Press, 2017)
Momoko Yamagata,1 Tome Ikezoe,1 Midori Kamiya,1 Mitsuhiro Masaki,2,3 Noriaki Ichihashi1 1Human Health Sciences, Graduate School of Medicine, Kyoto University, Kyoto, 2Department of Physical Therapy, 3Institute for Human Movement and Medical Sciences, Niigata University of Health and Welfare, Niigata, Japan Purpose: Sample entropy (SampEn) is an analysis to evaluate movement complexity of the center of pressure (COP). A lower value of SampEn indicates lower complexity of COP variability, that is, rigidity, and lower degrees of freedom. Previous studies reported the association of increased SampEn with improved standing balance ability in young subjects. However, no studies have examined these relationships among older adults. Thus, we aimed to investigate the relationship between SampEn and standing balance ability in older adults.Subjects and methods: The subjects were 33 institutionalized older adults (aged 82.2±6.5 years). COP during static standing was measured. The standard deviation (SD) values of COP and SampEn in the sagittal and frontal planes were calculated using time series data. One-leg standing test (OLST), functional reach (FR) test, and lateral reach (LR) test were also measured to evaluate standing balance ability.Results: OLST, FR, and LR were 6.5±8.3 s, 19.8±5.9 cm, and 18.2±6.4 cm, respectively. Pearson correlation analysis revealed that SampEn in the sagittal plane significantly correlated with OLST (r=-0.35) and FR (r=-0.36). However, SampEn in the frontal plane and SD of COP in both sagittal and frontal planes had no relationship with any of the clinical balance tests.Conclusion: Lower SampEn implies rigidity for postural control. In the present study, it was found that lower SampEn in the sagittal plane was related to a higher balance function, which suggests that older adults utilized body rigidity to maintain postural stability as a compensative strategy. Keywords: older adults, posture, balance, standing, complexity, entropy